The Health Education On Diarrhea And Constipation At The Al-Amin Islamic Boarding School In The Beringin Village, Barito Kuala - Muflih, Anhar; Kusumawati, Rahanda; Wulandari, Desy Ramadani; Ahdyani, Risa (Universitas Muhammadiyah Ahmad Dahlan Cirebon, 2025)
Islamic boarding schools are educational institutions based on Islamic principles. As educational institutions, Islamic boarding schools play a role in providing health education to raise awareness of the importance of maintaining good health within the boarding school environment. This educational activity aims to provide learning about diarrhea and constipation through lectures, demonstrations, and question-and-answer (QnA) sessions, as well as utilizing powerpoint presentations and leaflet to enhance the understanding of the female students. This community service activity was conducted on Tuesday, June 21, 2022, at the Al-Amin Girls’ Islamic Boarding School in Beringin Village, Barito Kuala. The study involved 30 female students from the Al-Amin Puteri Islamic Boarding School. The health education activity on diarrhea and constipation was conducted smoothly and successfully. Through this activity, the female students gained knowledge and understanding about diarrhea and constipation.